2023
DOI: 10.3390/life13102056
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis from Newborn to Adult—Epidemiology, Pathological Aspects, and Risk Factors

Alina Costina Luca,
Simona Georgiana David,
Alexandru Gabriel David
et al.

Abstract: Cardiovascular disease is the leading cause of mortality and morbidity throughout the world, accounting for 16.7 million deaths each year. The underlying pathological process for the majority of cardiovascular diseases is atherosclerosis, a slowly progressing, multifocal, chronic, immune-inflammatory disease that involves the intima of large and medium-sized arteries. The process of atherosclerosis begins in childhood as fatty streaks—an accumulation of lipids, inflammatory cells, and smooth muscle cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Although it is impossible to determine the exact cause of this small increase, it could be due to external factors such as diet and physical activity, which were not monitored. As for the lipid and hsCRP results, these decreases are particularly meaningful given the prevalence and long progression of cardiovascular diseases through the human lifespan [ 19 ]. Decreases in LDL cholesterol can help reduce major vascular events [ 20 ], and having low hsCRP, defined as <2 mg/L, can have protective effects against stroke and coronary heart disease [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is impossible to determine the exact cause of this small increase, it could be due to external factors such as diet and physical activity, which were not monitored. As for the lipid and hsCRP results, these decreases are particularly meaningful given the prevalence and long progression of cardiovascular diseases through the human lifespan [ 19 ]. Decreases in LDL cholesterol can help reduce major vascular events [ 20 ], and having low hsCRP, defined as <2 mg/L, can have protective effects against stroke and coronary heart disease [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that most study emphasized early resumption of antithrombotic agents after surgical intervention for chronic subdural hematoma. Because cardiovascular disease is the major cause of death for old age [ 6 ], the author argued that continuous use of antithrombotic agent is recommended for prevention of averse cardiovascular events after surgical intervention.…”
Section: Balancing Bleeding Risk and Thromboembolic Complications In ...mentioning
confidence: 99%
“…Approximately 10% of males aged 40 years already have well-developed atherosclerotic plaques, and by the age of 60 years, atherosclerosis is diagnosed in more than half of them [ 14 , 15 ]. Environmental factors play an essential role in the rate of development of atherosclerotic lesions; therefore, effective cardiovascular prevention programs are crucial in the management of these diseases [ 16 , 17 , 18 ]. Despite the implementation of recommendations regarding diet and physical activity, as well as pharmacotherapy for the management of cardiovascular risk factors, atherosclerosis is a progressive disease in more than 80% of people [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%